Intra-household decisions on cookstove choices and impacts on the welfare of women and girls - Mekonnen, Dawit Kelemework; Arega, Tiruwork; Yimam, Seid (Applied Research Programme on Energy and Economic Growth, 2022)
This study aimed to examine the intra-household decision-making on stove choice and understand whether the gender and other characteristics of the household member who decides on the type of cookstove used affect the intended welfare gains for women and girls. Using a nationally representative data set collected by the World Bank in 2018, factors associated with cookstove choices and the impact of the chosen cookstove type on women’s time use were estimated using a generalized structural equation modelling. The findings show that cookstove choices are associated more with the characteristics of the person who makes such decisions within the household than the characteristics of the head of the household. When the person who decides on the types of stoves used in the house is female, literate, married, cooks frequently in the house, and is employed, they are more likely to choose manufactured and self-built stoves. Women and girls in households that use a combination of manufactured and self built stoves spend less time on cooking and collection of fuel for home use and more time on childcare and paid work outside the house compared to women and girls in households that use only open fire tripod stoves. The stacking of manufactured, self built, and open fire tripod stoves frees up women's and girls' time for schoolwork by reducing cooking time, though it increases time they spend on fuel collection. Education and extension campaigns aimed at improving the adoption of improved cookstoves in rural Ethiopia would be more successful if they first identified who in the household makes the decision on cookstove choices and then focused their messaging to those persons, who are not always household heads. Cookstove program implementers will have a higher chance of convincing people to adopt self-built and manufactured stoves instead of open-fire stoves if their messaging focuses more on female members of households rather than male members, on those household members who cook frequently rather than those who cook only sometimes, and focus on educated rather than non-educated members of the household.